Cultural Perceptions of Gender Roles and their Influence on Career Choices in Religious Communities in United Kingdom - Clarke, Hannah (International Journal of Culture and Religious Studies, 2025)
Purpose: The purpose of this article was to analyze cultural perceptions of gender roles and their influence on career choices in religious communities in United Kingdom. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Cultural perceptions of gender roles in religious communities in the UK strongly influence career choices. Women are often expected to prioritize family over career, limiting their professional aspirations, especially in conservative religious groups. Men, on the other hand, are typically encouraged to pursue leadership and high-status careers. However, there is a growing shift, with more women entering the workforce, particularly in fields like healthcare and education. This reflects the tension between traditional gender norms and modern career opportunities in religious settings. Unique Contribution to Theory, Practice and Policy: Social role theory, cultural capital theory & expectancy theory expectancy may be used to anchor future studies on the cultural perceptions of gender roles and their influence on career choices in religious communities in United Kingdom. In practice, religious communities can take concrete steps to create environments that support equal career opportunities for men and women. From a policy perspective, religious institutions can implement gender-inclusive policies that promote equality in career choices.